Impact of uncontrolled hypertension on 12-month clinical outcomes following below-the-knee arteries (BTK) interventions in patients with critical limb ischemia. Issue 1 (December 2015) - Im, Sung; Rha, Seung-Woon; Choi, Byoung; Choi, Se; Lee, Jae; Lee, Sun; Kim, Ji; Na, Jin; Choi, Cheol; Lim, Hong; Kim, Jin; Kim, Eung; et al.
Abstract Background Despite intensive anti-hypertensive treatment, overall control rates of only 30 50 % have been reported in patients with hypertension (HTN). However, clinical significance and angiographic characteristics of patients with uncontrolled HTN following Below-the-knee arteries (BTK) interventions in patients with critical limb ischemia (CLI) are not clarified yet as compared to those with controlled HTN. Methods A total 165 consecutive hypertensive patients with BTK lesions from August 2004 to November 2012 were enrolled for this study. Uncontrolled HTN was defined as a blood pressure of > 140 mmHg systolic and 90 mmHg diastolic under anti-hypertensive treatment. A total of 112 patients (67.8 %) had uncontrolled HTN. We compared the clinical and angiographic characteristics of patients with uncontrolled HTN following BTK interventions to those with controlled HTN at 12-month follow-up. Results The baseline characteristics are well balanced between the two groups. At 12 months, there was no difference in the incidence of mortality, target lesion revascularization (TLR), target extremity revascularization (TER), and limb salvage rate in both groups. However, amputation rates were higher in patients with controlled HTN (33.9 vs. 19.6 %, P = 0.045). Conclusion Regardless of blood pressure control, HTN itself was an independent risk factor for BTK lesions, suggesting more intensive medical therapy with close clinical follow up will be required for all BTK patients with HTN.